Analysis of Factors That Influence Labor Absorption in The Selayar Islands Regency - Kasrina; Nursini; Hamrullah (Lafadz Jaya Publisher, 2023)
This study aims to analyze the effect of regional capital expenditure on employment both directly and indirectly through the level of education in the Selayar Islands Regency and the effect of wages on labor absorption in the Selayar Islands Regency in 2007-2020. This study used secondary data obtained from the Central Statistics Agency (BPS), the Manpower and Transmigration Service (DISNAKERTRANS). The data analysis model uses the TSLS (Two Stage Least Square) multiple liniear regression analysis model. The results of this study show that regional capital expenditure does not affect the absorption of labor either directly or indirectly in the Selayar Islands Regency while wages affect the absorption of labor in the Selayar Islands Regency.